Phosphonium polymethacrylates for siRNA delivery: effect of polymer and RNA structural parameters on polyplex assembly and gene knockdown - Loczenski Rose, Vanessa; Shubber, Saif; Sajeesh, S.; Spain, Sebastian G.; Puri, Sanyogitta; Allen, Stephanie; Lee, Dong-Ki; Winkler, G. Sebastiaan; Mantovani, Giuseppe (American Chemical Society, 2015)
Synthetic polymers containing quaternary phosphonium salts are an emerging class of materials for the delivery of oligo/polynucleotides. In this work, cationic phosphonium salt-containing polymethacrylates –and their corresponding ammonium analogues– were synthesized by RAFT polymerization. Both the nature of the charged heteroatom (N vs. P) and the length of the spacer separating the cationic units along the polymer backbone (oxyethylene vs. trioxyethylene) were systematically varied. Polymers efficiently bound siRNA at N+/P- or P+/P- ratios of 2 and above. At a 20:1 ratio, small polyplexes (Rh: 4-15 nm) suitable for cellular uptake were formed that displayed low cytotoxicity. Whilst siRNA polyplexes from both ammonium and phosphonium polymers were efficiently internalised by GFP-expressing 3T3 cells, no knockdown of GFP expression was observed. However, 65% Survivin gene knockdown was observed when short interfering RNA (siRNA) was replaced with novel, multimerised long interfering liRNA (liRNA) in HeLa cells, demonstrating the importance of RNA macromolecular architecture on RNA-mediated gene silencing.